2019 IEEE 21st International Workshop on Multimedia Signal Processing (MMSP) 2019
DOI: 10.1109/mmsp.2019.8901798
|View full text |Cite
|
Sign up to set email alerts
|

Insect interaction analysis based on object detection and CNN

Abstract: Direct observation to study biodiversity can be time consuming, however, other methods often provide indirect measurements and are possibly biased. To solve these problems, images can be a useful tool and ecologists have started to rely more and more on images as a source of data and on automated image analysis. However, the existing methods mostly perform image classification. In this paper we present an efficient method based on object detection to access deeper information the content of an image. Using hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In Lyu et al [25], the pictures of the desired insects were taken in the laboratory. While Yang et al [26] used Zhongwei Kechuang industrial cameras installed in field, other authors [27]- [29] used digital mobile cameras. Currently, Du et al [30] use high-resolution UAV, and Bjerge et al [31] use previously constructed portable computer versions, while Ard et al [32] use a Scoutbox along with a camera, and Rustia et al [33] use a wireless image monitoring system.…”
Section: On-site Images (Field or Laboratory)mentioning
confidence: 99%
“…In Lyu et al [25], the pictures of the desired insects were taken in the laboratory. While Yang et al [26] used Zhongwei Kechuang industrial cameras installed in field, other authors [27]- [29] used digital mobile cameras. Currently, Du et al [30] use high-resolution UAV, and Bjerge et al [31] use previously constructed portable computer versions, while Ard et al [32] use a Scoutbox along with a camera, and Rustia et al [33] use a wireless image monitoring system.…”
Section: On-site Images (Field or Laboratory)mentioning
confidence: 99%
“…Later Xia et al (2018) obtained a detection accuracy of 0.76 for their CNN of sea cucumber species on model-unseen internet images, and that of Tresson et al (2019) detected and identified individuals and castes of 23 ant species to a detection accuracy of 0.88.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…One solution is to slice the large input image and perform detection on slices separately before merging all results. This method can be used for satellite imagery analysis [16] or insect detection for example [17].…”
Section: Small Object Detectionmentioning
confidence: 99%
“…With large input images, detection might require a preprocessing phase. For this step we propose to apply an approach based on the method proposed by Tresson et al [17]. The pre-processing step is summarized in Algorithm 1.…”
Section: A Object Detectionmentioning
confidence: 99%